Gerindra’s ‘Gemoy’ Digital Democracy: Fragmenting the Public Sphere in Election 2024 - Fitri Sarasati; Tri Wahyuti; Andi Faisal Bakti; Rashmi Ranjan Panigrahi (LPPM Universitas PGRI Sumatera Barat, 2024)
This study investigates the transformation of political communication in Indonesia’s 2024 Presidential Election through Gerindra’s viral ‘Gemoy’ campaign, which employed emotionally resonant digital content to construct a relatable image of candidate Prabowo Subianto. Grounded in the frameworks of Viral Democracy Syndrome, Normalization and Illusion of Participation, and Fragmented Public Sphere theory, the research examines how algorithmic curation, affective aesthetics, and symbolic engagement contribute to democratic disillusionment and discursive fragmentation. Using a positivist-quantitative approach, data were collected via structured questionnaires from 200 purposively selected respondents Indonesian voters exposed to ‘Gemoy’ content. Statistical analyses, including regression and ANOVA, reveal three key findings. First, audience expectations for digital democracy significantly predict digital normalization experiences (R² = .438), indicating an “expectation-disillusionment paradox” wherein higher democratic hopes lead to increased recognition of symbolic manipulation. Second, a dual-pathway effect shows that while digital democracy initially reduces perceived fragmentation, normalization experiences strongly increase it (R² = .499), highlighting how algorithmic logic fosters echo chambers, polarization, and discourse trivialization. Third, initial exposure modality to ‘Gemoy’ content explains 87.5% of the variance in digital democracy expectations, validating the “platform determinism” hypothesis and illustrating how algorithmic architectures precondition political perceptions. The study concludes that while the ‘Gemoy’ strategy achieved short-term viral success, it also triggered long-term democratic deficits by programming audience consciousness and degrading deliberative engagement. This research contributes to the digital political communication literature by demonstrating the psychological and structural consequences of symbolic campaigns in Southeast Asia. It recommends policy interventions on algorithmic transparency, critical digital literacy beyond fact-checking, and the creation of deliberative digital spaces. Future research should explore longitudinal effects of viral political strategies and develop interdisciplinary models of technologically mediated political cognition.